2001
DOI: 10.1086/323981
|View full text |Cite
|
Sign up to set email alerts
|

Infections withEhrlichia chaffeensisandEhrlichia ewingiiin Persons Coinfected with Human Immunodeficiency Virus

Abstract: The clinical course and laboratory evaluation of 21 patients coinfected with human immunodeficiency virus (HIV) and Ehrlichia chaffeensis or Ehrlichia ewingii are reviewed and summarized, including 13 cases of ehrlichiosis caused by E. chaffeensis, 4 caused by E. ewingii, and 4 caused by either E. chaffeensis or E. ewingii. Twenty patients were male, and the median CD4(+) T lymphocyte count was 137 cells/microL. Exposures to infecting ticks were linked to recreational pursuits, occupations, and peridomestic ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
146
3
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 157 publications
(152 citation statements)
references
References 47 publications
2
146
3
1
Order By: Relevance
“…11 Two studies have demonstrated the high clinical sensitivity of PCR in patients when the organism was concurrently isolated from the blood or in patients co-infected with human immunodeficiency virus. 11,15,24 However, in another study, a substantial number of confirmed cases of HME had undetectable ehrlichial DNA by PCR. 25 Because of the limited data available and lack of a standard PCR protocol, current recommendations for the diagnosis of HME suggest that PCR is a valuable adjunct to IFA.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…11 Two studies have demonstrated the high clinical sensitivity of PCR in patients when the organism was concurrently isolated from the blood or in patients co-infected with human immunodeficiency virus. 11,15,24 However, in another study, a substantial number of confirmed cases of HME had undetectable ehrlichial DNA by PCR. 25 Because of the limited data available and lack of a standard PCR protocol, current recommendations for the diagnosis of HME suggest that PCR is a valuable adjunct to IFA.…”
Section: Discussionmentioning
confidence: 98%
“…15,19 E. canis-infected dogs were experimentally inoculated and monitored for ehrlichiae in peripheral blood by PCR amplification of the p28 gene. PCR of E. canis p28 was conducted by the Louisiana State University Veterinary Medical Diagnostic Laboratory using primers ECa282F239, 5Ј-CAA GCA GCA GCC ACA CAA T-3Ј (forward), and ECa28R701, 5Ј-GAT GCT TCT GGG CTT ATG GAG TA-3Ј (reverse), with thermal cycling protocol of 10 minutes at 95°C, 40 cycles of 95°C for 30 seconds, 50°C for 1 minute, and 72°C for 1 minute and finished with 10 minutes at 72°C as previously described.…”
Section: Species-specific Detection Of Ehrlichia In Cases Of Natural mentioning
confidence: 99%
See 2 more Smart Citations
“…A rapid and inexpensive method to diagnose ehrlichiosis is by identification of morulae on Wright's-stained peripheral blood films. The literature regarding the prevalence of and morphologic descriptions of peripheral blood films containing infected white blood cells in confirmed cases of ehrlichiosis is limited, 21 so the detection rate and Figure 1 Atypical lymphocytes were more commonly seen in Ehrlichia-infected cases. They were typically large, with hyperchromatic nuclei, abundant basophilic cytoplasm, and contained prominent cytoplasmic granules (Wright's-stained blood film, patient 6, original magnification  300).…”
Section: Discussionmentioning
confidence: 99%